Assertive Communication Intervention to Improve Communication Skills in Adolescents with Emotional and Behavioral Disorders: Needs Analysis - L Rahmadani Fatimah; Ahsan Romadlon Junaidi; Ediyanto Ediyanto (Jurnal ORTOPEDAGOGIA, 2025)
This study aims to identify the need for interventions to reduce social anxiety among adolescents with emotional and behavioral disorders (EBD) through an assertive communication approach. High levels of social anxiety can hinder adolescents social, emotional, and academic functioning, particularly in situations involving social interaction and peer evaluation. This research employed a descriptive quantitative approach using a needs assessment survey involving junior high school students and teachers. The instrument used was a questionnaire developed based on indicators of social anxiety and assertive communication competence. The findings indicate that most respondents acknowledged the need for assertive communication-based interventions, with complementary techniques such as journaling and role-playing. This intervention is considered relevant and aligned with the inclusive education principles in the Merdeka Curriculum. The results highlight the importance of developing contextual, adaptive, and evidence-based intervention programs to address social anxiety in adolescents with EBD.